THE IMAGE OF THE HORSE AND AESTHETIC VIEWS IN MUQIMI'S LITERARY CREATIVITY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article is devoted to the analysis of a sample of the satirical work of the outstanding Uzbek poet of the 19th century, Mukimiy. The poet's skill in criticizing socio-political problems, the style of creating a satirical image, and his own unique aspects are studied. By analyzing one of Mukimiy's satirical ghazals, artistic interpretations of the vices and shortcomings of society are discovered.